Democracy in the United States: An Analysis of its Evolution and Challenges - Kelvin Alfonso (GoAcademica Research & Publishing, 2023)
Democracy in the United States has served as a model for many nations around the world. This article explores the historical evolution of democracy in the United States, its core principles, and the contemporary challenges it faces. The United States has been a beacon of democracy for over two centuries, yet it grapples with issues such as political polarization, voter suppression, and the role of money in politics. Understanding the evolution and challenges of American democracy can shed light on the broader global discourse surrounding democratic governance.